A compact dual‐band filtering antenna for wireless local area network applications. Issue 9 (13th May 2019) - Deng, Jing‐Ya; Tan, Chong‐Hao; Hou, Si‐Min; Sun, Dong‐Quan; Guo, Li‐Xin
Abstract: A printed dual‐band filtering antenna with decent frequency selectivity at 2.45 and 5.2 GHz for wireless local area network (WLAN) applications is developed. The filtering antenna is compact, which comprises a tapped feed line, two dual‐band stub‐loaded open‐loop resonators, and a dual‐band bended monopole. It can be easily printed on a single layer PCB substrate with low profile and low cost. The entire structure is very simple compared with the previously reported dual‐band filtering antennas that requiring multi‐layer structures. The monopole functions as not only a radiator, but also the last resonator of a dual‐band filter. The developed antenna exhibits good frequency selectivity and out‐of‐band suppression. In addition, the two operation bands can be adjusted relatively individually. The proposed antenna is optimized and fabricated. The experimental results show it has good frequency selectivity at both 2.45 and 5.2 GHz, wide bandwidth 11.8% and 7.8%, and excellent out‐of‐band suppression.